Snowed in for Christmas - Morgan, Sarah (Romance fiction writer) (Harlequin Books, 2022)
"A FAMILY GATHERING. This Christmas, the Miller siblings have one goal--to avoid their well-meaning family's prying questions. Ross, Alice and Clemmie have secrets that they don't intend to share, and they are relying on each other to deflect attention. AN UNIVITED GUEST. Lucy Clarke is facing a Christmas alone and the prospect of losing her job. Unless she can win a major piece of business from Ross Miller, the season promises to be anything but festive. She'll just deliver her proposal to his family home and then leave. After all, she wouldn't want to intrude on the Miller family's perfect Christmas. A CHRISTMAS TO REMEMBER. When Lucy appears on the Miller family's snow-covered Highland doorstep, she's mistaken for Ross's girlfriend. By the time the confusion is cleared up, they're snowed in--she can't leave, even if she want to! But does she want to? As secrets spill out like presents from an overstuffed stocking and the chemistry between her and Ross ignites, this is going to be either Lucy's worst Christmas ever or the best mistake of her life."--Jacket flap.